The Influence of Greek Philosophy on The Development of Arabic Grammar - Mahyudin Ritonga (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
This paper is intended to disclose the interrelationship between Greek philosophy with the development of nahwu. The research is based on literature data, and the collected data are classified and analyzed using inductive and comparative method. The research results show that nahwu development is not apart from the influence of philosophy. The interconnection has occurred since the period of al-Muqaffa who has translated many works of Aristotle and Plato which al-Khalil makes as reference in arranging nahwu principles. The influence of philosophy on nahwu can be identified in two things, which are in methodological and terminological aspects.